THE TRANSITION FROM PERALUMINOUS TO PERALKALINE GRANITIC MELTS: EVIDENCE FROM MELT INCLUSIONS AND ACCESSORY MINERALS - Thomas R.; Rhede D.; Seifert W.; Rickers K.; Heinrich W.; Webster J.D.; Förster H.-J.; Davidson P. (My University, 2006)
Fractional crystallization of peraluminous F- and H2O-rich granite magmas progressively enriches the remaining melt with volatiles. We show that, at saturation, the melt may separate into two immiscible conjugate melt fractions, one of the fractions shows increasing peraluminosity and the other increasing peralkalinity. These melt fractions also fractionate the incompatible elements to significantly different degrees. Coexisting melt fractions have differing chemical and physical properties and, due to their high density and viscosity contrasts, they will tend to separate readily from each other. Once separated, each melt fraction evolves independently in response to changing T/P/X conditions and further immiscibility events may occur, each generating its own conjugate pair of melt fractions. The strongly peralkaline melt fractions in particular are very reactive and commonly react until equilibrium is attained. Consequently, the peralkaline melt fraction is commonly preserved only in the isolated melt and mineral inclusions. We demonstrate that the differences between melt fractions that can be seen most clearly in differing melt inclusion compositions are also visible in the composition of the resulting ore-forming and accessory minerals, and are visible on scales from a few micrometers to hundreds of meters. © 2006 Elsevier B.V. All rights reserved.
Keywords: ACCESSORY MINERALS; GRANITE MELTS; MAGMA EVOLUTION; MELT INCLUSIONS; MELT-MELT IMMISCIBILITY; PERALKALINITY; PERALUMINOSITY